2021
DOI: 10.25124/jmi.v21i3.3439
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Training Results Perception on Individual Work Performance of Employee Moderated by Intrinsic and Extrinsic Motivation

Abstract: This study aims at examining the effect of training results perceptions on individual work performance of employee, and intrinsic and extrinsic motivation serving as moderation strengthening that effect. T his study was quantitative research selecting 453 samples out of 1.311 population from PT KAI’s employees in which they are executive officer. The data collection was done using a close questionnaire with Likert scale 1-5. All valid and reliable instruments were assessed through Factor Analysis and Cronbach'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The existence of motivation will trigger employees to work harder to affect the company in achieving its goals (Rivai, 2004). Turachma & Hendarsjah (2021) found that extrinsic motivation influenced employee performance. The higher the motivation in employees, the better the performance it produces.…”
mentioning
confidence: 99%
“…The existence of motivation will trigger employees to work harder to affect the company in achieving its goals (Rivai, 2004). Turachma & Hendarsjah (2021) found that extrinsic motivation influenced employee performance. The higher the motivation in employees, the better the performance it produces.…”
mentioning
confidence: 99%